The Cathedral of Split in the Early Middle Ages (Archaeologia Adriatica, 2010)
The temple of Jupiter at Diocletian’s palace in Split, which at the same time was also the mausoleum of the emperor, was transformed in the early medieval period into a cathedral dedicated to the Virgin Mary, otherwise much better known under the name of St. Domnius, the patron saint of the city. Changes in the function of the structure were reflected in the following:
Keywords: Split; cathedral; early Middle Ages; liturgical furnishings